Sistemas de numeração e grandezas incomensuráveis - Ruis, André Valner [UNESP] (2014)
In this work, we present the historical evolution of the concept of real number. From the preliminary sense of quantifications we introduce numerical systems, specially the decimal one and the ternary one. From the measure problem we introduce the concept of commensurable and incommensurable magnitudes. It is given special emphasis to the irrational numbers e and π, for which we discuss the concepts, properties and some particularities. Moreover, we discuss how to introduce the study of irrational numbers at high school and we propose some activities connected to the presented themes